Analysis of Customer Satisfaction Level on Service Quality Price Service and Word of Mouth - Budari, Hadijah; Rasyid, Abdul; Ameliana, Yana (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study examines the effect of Service Quality, Price, and Word of Mouth (WOM) on Customer Satisfaction at the Cahaya Berkah Jayapura Workshop. Research Design and Methodology: This study uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to 100 customers of Cahaya Berkah Workshop, which were selected using incidental techniques. Multiple linear regression analysis was used to test the effect of independent variables (Service Quality, Price, and WOM) on the dependent variable (Customer Satisfaction). Validity and reliability tests were conducted to ensure the research instruments were valid and consistent. Findings and Discussion: The results showed that Service Quality, Price, and WOM significantly affect Customer Satisfaction both partially and simultaneously. The three independent variables jointly affect customer satisfaction. These findings support classic marketing theory and align with previous research, suggesting that good service quality, competitive prices, and positive WOM can increase customer satisfaction. Implications: This research makes a significant contribution to marketing literature and business practice. From the scientific side, this research enriches the understanding of the determinants of customer satisfaction in the automotive industry. In terms of practice, the findings guide the management of the Cahaya Berkah Workshop and other workshops in increasing customer satisfaction through improved service quality, reasonable pricing, and effective utilization of WOM. Limitations of this study include the narrow geographical coverage and cross-sectional nature of the data, which provide opportunities for further research with a longitudinal approach and broader coverage.